Sewing stylish handbags & totes : chic to unique bags and purses that you can make - Knight, Choly (Design Originals, 2013)
"Bags can be functional, stylish, colorful, or whimsical. This book shows you how to sew your own one-of-a-kind bags to satisfy all your needs and tastes. Create personalized bags that range from sophisticated to indispensable. Learn the basics of bag sewing techniques, and get tips for going green with upcycled found fabrics. We demystify the bells and whistles that go into designer bags so that you can craft your own with the same flair... but not the same price! Whether you want your bag plain and simple or detailed and complex, you'll find plenty of fun options, motifs, and ideas to get you started. Sew Stylish Handbags will guide you to create a bag that just makes your life a little easier, or a truly show-stopping piece of arm candy that really puts an outfit together. So let your imagination go wild and get sewing! Discover how to make your own one-of-a-kind bags that are quirky, modern and fun! -Get step-by-step instructions for making over 50 useful & stylish bags. -Learn the basics of fabric selection, sewing techniques, tools, hardware, and supplies. -Recreate the high-end look of designer bags at a fraction of the cost. -Discover stylish motifs that will make you look like you spent hundreds on your bag. -Go green with handmade reusable bags, upcycled found fabrics, and recycled materials. -Make a Retro Messenger Bag, Collapsible Shopping Tote, Technophile Laptop Bag, On the Town Errand Bag, and many more! "--